CONTAMINATION WITH TOXOCARA SPP. EGGS OF ENVIRONMENTAL SAMPLES OF PUBLIC PLACES OF VARNA CITY, BULGARIA - Tatyana Cvetkova; Kalina Stoyanova; Tsonko Paunov (Peytchinski Publishing, 2018)
Toxocariasis in humans is an unknown and underdiagnosed disease with increased risk of distribution determined by the large canine and cat populations. Contamination of the environment with pets faeces containing helminth eggs is the key route of transmission toxocariasis, threatening especially the youngest children. The purpose of this study is preliminary research of the degree of pollution of the environment with Toxocara spp. eggs by examining soil and sand samples from different public places of Varna, Bulgaria. Material and methods: In 2018, 40 soil and sand samples were collected from various locations of Varna city: public park areas, areas for dog-walking, playgrounds, sandboxes and yards with domestic animals. The samples were processed using a modified Romanеnko's method. Results: Soil analysis showed Toxocara spp. eggs in one sample from a public park area in the central region of Varna. In another soil sample of a private yard with domestic dog typical ova of the Taeniidae family was observed (possibly of E. granulosus). In two other samples, eggs from other canine parasites were discovered. Conclusion: The first research on the environmental contamination with helminthic eggs in Northeastern Bulgaria showed Toxocara spp. eggs in one of the central and most populated areas of Varna city. Furthermore, at least 10% of the tested materials were contaminated with canine excrements that testify for the lack of proper control of domestic and stray animals, which represents a real and imminent danger from zoonotic infection for the public health in the region.